Cellulose Based Photonic Materials Displaying Direction Modulated Photoluminescence - Santos, Molíria V. [UNESP]; Maturi, Fernando E. [UNESP]; Pecoraro, Édison [UNESP]; Barud, Hernane S.; Lima, Laís R. [UNESP]; Ferreira, Rute A. S.; Carlos, Luís D.; Ribeiro, Sidney J. L. [UNESP] (Frontiers, 2021)
Photonic materials featuring simultaneous iridescence and light emission are an attractive alternative for designing novel optical devices. The luminescence study of a new optical material that integrates light emission and iridescence through liquid crystal self-assembly of cellulose nanocrystal-template silica approach is herein presented. These materials containing Rhodamine 6G were obtained as freestanding composite films with a chiral nematic organization. The scanning electron microscopy confirms that the cellulose nanocrystal film structure comprises multi-domain Bragg reflectors and the optical properties of these films can be tuned through changes in the relative content of silica/cellulose nanocrystals. Moreover, the incorporation of the light-emitting compound allows a complementary control of the optical properties. Overall, such findings demonstrated that the photonic structure plays the role of direction-dependent inner-filter, causing selective suppression of the light emitted with angle-dependent detection.
Keywords: bacterial cellulose nanocrystals; chiral nematic liquid crystal; iridescence; luminescence; modulated light emission; photonic materials; rhodamine 6G